A Participatory Investigation of Bovine Health and Production Issues in Pakistan - Ghafar, Abdul; McGill, David; Stevenson, Mark A.; Badar, Muhammad; Kumbher, Aijaz; Warriach, Hassan M.; Gasser, Robin B.; Jabbar, Abdul (Frontiers in Veterinary Science, 2020)
Systems to record the frequency of animal health events in Pakistan are limited. A participatory approach was used to address gaps in farmers’ knowledge and understanding of bovine health and production issues in five agroecological zones (AEZs) of Pakistan. Participatory tools, including simple ranking, pairwise ranking, constraint impact scoring and constraint profiling were used in group discussions with farmers and animal health professionals (AHPs) in six districts of two provinces, Punjab and Sindh. The results of the ranking activities showed that foot-and-mouth disease (FMD), clinical mastitis, ticks, haemorrhagic septicaemia, reproductive disorders, blackleg and endoparasites were the most important bovine health and production constraints for small-scale dairy farmers. Constraint impact scoring showed that the participants perceived that: (1) milk production was severely affected by FMD and mastitis; (2) blackleg and parasitism led to poor growth rates and reduced meat production; (3) reproductive disorders and mastitis caused major economic losses (due to the high cost of treatment); and (4) blackleg and hemorrhagic septicemia were the leading causes of mortality in cattle and buffaloes. Although there was strong agreement in responses and constraint impact scores between farmers and AHPs, farmers were more concerned about health issues that cause high mortalities, whereas AHPs emphasised the importance of disorders with a high economic impact. Despite socioeconomic differences among AEZs, farmers’ knowledge about bovine health and production constraints was similar. The findings from this study revealed that farmers had limited understanding of the risk factors and routes of transmission of various infectious diseases of bovines, which emphasizes the need to develop and implement tailored extension programs in Pakistan to control contagious diseases of animals and to improve the profitability of small-scale dairy farmers.